1996
DOI: 10.1104/pp.111.4.1199
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Plasma Membrane H+-ATPase in K+ Transport

Abstract: The role of the plant plasma membrane H+-ATPase in K+ uptake was examined using red beet (Befa vulgaris 1.) plasma membrane vesicles and a partially purified preparation of the red beet plasma membrane H+-ATPase reconstituted in proteoliposomes and planar bilayers. For plasma membrane vesicles, ATP-dependent K+ efflux was only partially inhibited by 1 O0 PM vanadate or 1 O PM carbonyl cyanide-ptrifluoromethoxyphenylhydrazone. However, full inhibition of ATP-dependent K+ efflux by these reagents occurred when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Similar mechanisms of cytosolic ATP in control of K 1 efflux have been reported in other plant cells, in which the outwardrectified K 1 channels were activated or completely abolished within 15 min in the presence or absence of cytosolic ATP (Spalding and Goldsmith, 1993;Briskin and Gawienowski, 1996;Goh et al, 2004). This response period is similar to that observed for changes in nodule permeability to oxygen diffusion, providing further support for the suggestion that cytosolic ATP-coupled K 1 movement is involved in the control of oxygen diffusion in legume nodules.…”
Section: The 10% O 2 Treatmentsupporting
confidence: 68%
“…Similar mechanisms of cytosolic ATP in control of K 1 efflux have been reported in other plant cells, in which the outwardrectified K 1 channels were activated or completely abolished within 15 min in the presence or absence of cytosolic ATP (Spalding and Goldsmith, 1993;Briskin and Gawienowski, 1996;Goh et al, 2004). This response period is similar to that observed for changes in nodule permeability to oxygen diffusion, providing further support for the suggestion that cytosolic ATP-coupled K 1 movement is involved in the control of oxygen diffusion in legume nodules.…”
Section: The 10% O 2 Treatmentsupporting
confidence: 68%
“…Taken together, the data suggest that lightdriven photosynthesis is not directly involved in the activation of K out channel current in the plasma membrane, although the possibility of direct K ϩ transport by other ATPases (i.e. K ϩ -ATPases) cannot be ruled out (17). Mitochondrial respiration therefore provides the source of cytosolic ATP.…”
Section: Discussionmentioning
confidence: 76%
“…The high-affinity transport system (HATS) is a saturable system catalyzing the thermodynamically active uptake of K + at low concentrations (o1 mM). The active influx of K + is thought to be coupled to the passive influx of H + down its electrochemical gradient, which is maintained by proton-pumping ATPase complexes in the plasma membrane (Cheeseman et al, 1980;Rodríguez-Navarro et al, 1986;Kochian et al, 1989; Maathuis and Sanders, 1994;Briskin and Gawienowski, 1996). Despite some disagreement concerning the precise stoichiometry of H + /K + symport, it is generally accepted to be 1:1 ( Maathuis and Sanders, 1994;Maathuis et al 1997), as has also been demonstrated in bacterial ( Bakker and Harold, 1980) and fungal systems (Rodríguez-Navarro et al, 1986).…”
Section: High-affinity K + Transportmentioning
confidence: 99%